Strategi Politik Nadiem Makarim dalam Mengembangkan Pendidikan - Cindy Amelia; Ainur Ropik; Hatta Azzuhri (Jurnal Prodi Ilmu Politik, 2023)
ABSTRACT This research is entitled "Nadiem Makarim's Political Strategy in Producing Education". Discusses the changes in education during the Nadiem Makarim era which had a political strategy as an action used by leaders to realize their political goals. The purpose of this study is to find out the strategy carried out by Nadiem Makarim as Minister of Education, Culture, Research and Technology in developing education in Indonesia. The theory used in this study is strategy theory according to Geoff Mulgan (2009) this strategy is useful as a system that can manage existing power and resources through government which aims for the public interest which is a tool of government power to create ideas and ideas in overcoming problems, complexities and government complex. This study uses data collection techniques through library research. The results of this study indicate that Nadiem Makarim uses an Offensive Strategy, namely a market expansion strategy in implementing new regulations, to carry out the program he has designed by determining what objectives Nadiem Makarim wants, what factors influence Nadiem Makarim in making programs, what directions Nadiem Makarim did, and what actions did Nadiem Makarim take to carry out his program to develop education in Indonesia Keywords : Strategy, Nadiem Makarim, Education